2021
DOI: 10.3802/jgo.2021.32.e13
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy combined with chemotherapy increases the risk of herpes zoster in patients with gynecological cancers: a nationwide cohort study

Abstract: Objective: This study aimed to determine the effect of radiotherapy (RT) on the risk of herpes zoster (HZ) in patients with gynecological cancers via a nationwide population-based study. Methods: Based on patient data obtained from the National Health Insurance Research Database, 1928 gynecological cancer patients were identified with 1:1 matching for RT and non-RT cohorts by age, index date, and cancer type. Another cohort consisting of 964 noncancer individuals matched was used as normal control. The inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(11 reference statements)
0
3
1
Order By: Relevance
“…However, we found CT itself had no effect on HZ (aHR: 1.47, p = 0.15), and the synergistic effect of CT was observed only in HN cancer patients who received RT. Contrastingly, in our previous work on gynecological cancer, we established that both CT and RT had significant roles in HZ development [18].…”
Section: Plos Onecontrasting
confidence: 90%
“…However, we found CT itself had no effect on HZ (aHR: 1.47, p = 0.15), and the synergistic effect of CT was observed only in HN cancer patients who received RT. Contrastingly, in our previous work on gynecological cancer, we established that both CT and RT had significant roles in HZ development [18].…”
Section: Plos Onecontrasting
confidence: 90%
“…64 In a population-based study, the authors have demonstrated that gynecological cancer patients receiving RT and CT had the highest cumulative risk of HZ compared with the non-RT group (1.68-fold higher risk of HZ; 95% CI 1.16-2.36, P ¼ 0.009). 65 This increased risk of HZ has also been confirmed in patients with head/neck cancer (18.55 versus 9.06 per 1000 person-years, P ¼ 0.03) and persisted within the first 2 years and then diminished. 66…”
Section: Hz and Radiotherapymentioning
confidence: 69%
“…In a population-based study, the authors have demonstrated that gynecological cancer patients receiving RT and CT had the highest cumulative risk of HZ compared with the non-RT group (1.68-fold higher risk of HZ; 95% CI 1.16-2.36, P = 0.009). 65 …”
Section: Hz In Cancer Patientsmentioning
confidence: 99%
“…One year after left nephroureterectomy, HZ occurred on the ipsilateral side, possibly due to decreased immunity resulting from various factors, including the operation itself. this case had many risk factors for PHN, including age > 50 years, history of solid tumor, diabetes, and renal insu ciency [11][12][13]. The characteristics of HZ in this patient were obvious prodromal pain, severe pain, a large herpes area, and an underlying disease accompanied by reduced immune function.…”
Section: Discussionmentioning
confidence: 98%